Ekonomi - K, Amiruddin; Muslihati; Estyanti , Chintya; Mu'min, Ali (LAA MAISYIR: Jurnal Ekonomi Islam, 2023)
Sharia banks have grown as a barometer of the success of the presence of the sharia economy, which has become an alternative form chosen by the public while conventional banks still exist and continue to operate. The purpose of this article is to review the concept of Sharia banking in the world of economics and business. The data collection method in this article is literature study. The research results found that the existence of banks with Islamic values ​​and norms aims to fulfill people's desires. As intermediaries and providers of financial services that operate on Islamic ethics and value systems, Sharia banks without unproductive speculative activities such as gambling (maysir), unclear and suspicious matters (gharar) and interest (riba) are developing in Asia, Europe, America and Australia. The factors driving the development of Sharia banks are increasing public awareness about halal lifestyles, government support including the formation of KNEKS and the evolution of digital technology driven by the emergence of social media influencers, one of which is in the form of preaching content.